2001
DOI: 10.1287/isre.12.3.225.9712
|View full text |Cite
|
Sign up to set email alerts
|

Research Commentary: Introducing a Third Dimension in Information Systems Design—The Case for Incentive Alignment

Abstract: P rior research has generated considerable knowledge on information systems design from software engineering and user-acceptance perspectives. As organizational processes are increasingly embedded within information systems, one of the key considerations of many business processes-organizational incentives-should become an important dimension of any information systems design and evaluation, which we categorize as the third dimension: incentive alignment. Incentive issues have become important in many IS areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(172 citation statements)
references
References 49 publications
(39 reference statements)
1
163
2
6
Order By: Relevance
“…ISSN 2162-3058 2013 It may be a reflection of male dominance in ICT industries. The two major age groups, 25 to 34 and 35 to 44, indicate that they believe knowledge sharing benefit them to improve work efficiency (Ba, Stallaert, and Whinston, 2001). The research findings revealed that most of the firms were either SMEs or larger companies.…”
Section: Discussionmentioning
confidence: 91%
“…ISSN 2162-3058 2013 It may be a reflection of male dominance in ICT industries. The two major age groups, 25 to 34 and 35 to 44, indicate that they believe knowledge sharing benefit them to improve work efficiency (Ba, Stallaert, and Whinston, 2001). The research findings revealed that most of the firms were either SMEs or larger companies.…”
Section: Discussionmentioning
confidence: 91%
“…When organizations publically acknowledge contributions from organizational members, they will be incentivized to report more messages to gain public recognition through their interaction with the KMS [24]. Attribution, a type of extrinsic reward [22], communicates to the individual that the organization values their contribution and assigns personal credit.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Thus, knowledge self-efficacy is a specific form of self-efficacy. Knowledge self-efficacy refers to individual believing that his or her knowledge can help to solve task-related problems [45], [46], improve work performance [46], and increase competitive advantage [47]. In this study, through contributing useful and valuable knowledge in response to others' questions, individual will increase their sense of virtual community and knowledge self-efficacy.…”
Section: B the Relationship Between The Sense Of Virtual Community Amentioning
confidence: 99%